Hologenome analysis of two marine sponges with different microbiomes - Ryu, Taewoo (BMC Genomics, 2016)
BACKGROUND: Sponges (Porifera) harbor distinct microbial consortia within their mesohyl interior. We herein analysed the hologenomes of Stylissa carteri and Xestospongia testudinaria, which notably differ in their microbiome content. RESULTS: Our analysis revealed that S. carteri has an expanded repertoire of immunological domains, specifically Scavenger Receptor Cysteine-Rich (SRCR)-like domains, compared to X. testudinaria. On the microbial side, metatranscriptome analyses revealed an overrepresentation of potential symbiosis-related domains in X. testudinaria. CONCLUSIONS: Our findings provide genomic insights into the molecular mechanisms underlying host-symbiont coevolution and may serve as a roadmap for future hologenome analyses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-2501-0) contains supplementary material, which is available to authorized users.